Fasciolopsis buski Vomited Out by a Child; The First Case Reported from Nepal - Pant, Narayan Dutt; Sharma, Manisha; Khatiwada, Saroj (Nepal Journal of Biotechnology, 2015)
Live adult worms of Fasciolopsis buski are rarely seen in humans except in autopsy. Only a few such cases have been reported in the world literature. We reported a case of fasciolopsiasis in a child of age 14 months who coughed out the live adult Fasciolopsis buski after administration of antihelminthic drug. The patient was a resident of Terai (Far Western) region of Nepal and had history of travelling to India. This is the first case of fasciolopsis reported from Nepal. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 66-67